Femoral transcatheter valve-in-valve implantation as alternative strategy for failed aortic bioprostheses: A single-centre experience with long-term follow-up. (1st May 2020) - Stankowski, Tomasz; Aboul-Hassan, Sleiman Sebastian; Seifi Zinab, Farzaneh; Herwig, Volker; Stępiński, Piotr; Grimmig, Oliver; Just, Soeren; Harnath, Axel; Muehle, Anja; Fritzsche, Dirk; Perek, Bartłomiej
Abstract: Background: Surgical reoperation is still a standard procedure performed for degenerated aortic bioprostheses. On the other hand femoral minimally invasive valve-in-valve implantation (femTAVI-VIV) is an intriguing alternative. This clinical study was design to compare the early and late outcomes of redo-surgery (Redo-AVR) and femTAVI-VIV procedures for failed aortic bioprostheses. Methods: We retrospectively reviewed 108 patients with degenerated aortic bioprostheses qualified for isolated Redo-AVR (n = 40) or femTAVI-VIV (n = 68) between 2003 and 2018. Both cohorts were divided into intermediate and high-risk groups according to the EuroSCORE II (4–9% and >9%). Propensity score matching selected 20 pairs in Intermediate-risk group and 10 pairs in High-risk group for the final comparison. Results: Patients qualified for femTAVI-VIV were older (79.2 vs 72.9 years, p < 0.001) and at higher risk (EuroSCORE II 10.9 vs 7.8%, p = 0.005) than Redo-AVR subjects. Overall survival in femTAVI-VIV and Redo-AVR was comparable at 30-days, 1- and 5-years, respectively (92.6% vs 92.5%, 85.2% vs 85.0% and 62.9% vs 72.5%, p = 0.287). After PSM no differences in mortality, myocardial infarction, pacemaker implantation, stroke or acute renal insufficiency were found. Transcatheter procedure was associated with shorter hospital stay, lower rate of blood products transfusions and higher incidence of mild paravalvular leaks. Conclusion: Our study supports the opinion that transcatheter approach for treatment of patients with degenerated aortic bioprostheses is a safe alternative to Redo-AVR procedures particularly for those at high-risk. Highlights: Self-expanding TAVI-VIV ensures comparable early and long-term outcomes to Redo-AVR. Femoral TAVI-VIV implantation is less invasive than conventional chest reopening. Femoral TAVI-VIV leads to a short hospital stay. Mild paravalvular leak after TAVI-VIV occurs more often than after Redo-AVR. FemTAVI-VIV is an excellent solution for high risk patient with failed bioprosthesis.